The relations among foreign language anxiety, academic buoyancy and willingness to communicate in EFL classroom - Lin, Yuxin; Wang, Baochang; Zhang, Guizhen; Su, Yankui (Frontiers in Psychology, 2025)
This study, grounded in the frameworks of Positive Psychological Resources Theory and Emotion Regulation Theory, investigated the mechanism through which foreign language anxiety (FLA) and academic buoyancy (AB) influence students' willingness to communicate (WTC) in EFL classroom. A mixed-methods approach was employed, combining a Structural Equation Modeling (SEM) analysis based on data from 627 senior high school students and semi-structured interviews with eight randomly selected participants in China. The empirical results indicate that FLA significantly and negatively predicts WTC, while AB plays a partial mediating role in this relationship, thereby validating the proposed “FLA—AB—WTC” path model. These results highlight academic buoyancy as a positive psychological trait that mediates the effect of anxiety on willingness to communicate. This research offers theoretical and practical implications for affective regulation and psychological empowerment in foreign language pedagogy.